Sinterability and electrical characterization of BaCe0.9Y0.1O3-δ: A discussion on intrinsic liquid-phase mechanisms - de Araujo Huyra Estevao (Processing and Application of Ceramics)
Yttrium-doped barium cerate (BaCe0.9Y0.1O3-δ, BCY) powders were synthesized via two powder processing routes: i) the conventional solid-state reaction and ii) modified wet chemical method. The influence of sintering schedules on densification mechanisms, microstructural evolution and electrical properties was systematically investigated. The results indicate that the intrinsic liquid-phase assisted sintering occurs in the samples prepared by both routes, but it is more prominent for the low-sinterability powder synthesized by solid-state reaction, leading to a more uniform microstructure and conductivity less dependent on sintering conditions. Electrical conductivity measurements revealed that the ceramics prepared via the wet chemical route exhibited superior proton conductivity at lower sintering temperatures, though with more significant variability depending on the processing conditions. The competition between solid-state and liquid-phase sintering significantly impacts densification and electrical performance. These findings highlight the critical role of processing routes and intrinsic liquid phase in tailoring the microstructure and optimizing the electrical properties of the BCY ceramics for electrochemical applications.